2007
DOI: 10.1536/ihj.48.369
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix Metalloproteinase Inhibitor, ONO-4817, Suppresses the Development of Aortic Intimal Hyperplasia in Experimental Hyperlipidemic Rabbit

Abstract: SUMMARYInhibition of matrix metalloproteinases (MMPs) would be expected to suppress atherosclerotic neointimal proliferation and thus limit atheromatous plaque progression, but this has not yet been demonstrated morphologically in atherosclerotic intimal hyperplasia induced by cholesterol loading in experimental animals. We therefore investigated whether a broad-spectrum MMP inhibitor (MMPi), ONO-4817, could inhibit the development of intimal hyperplasia in male hyperlipidemic rabbits (n = 6) fed laboratory ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There is evidence [24][25][26] that increased MMP expression is associated with the development of neointimal lesions after arterial balloon injury in experimental animals. MMP inhibitor can suppress the development of intimal hyperplasia in hyperlipidemic rabbits [27]. However, other studies have demonstrated that doxycycline, a broadspectrum MMP inhibitor, has negligible effects on the development of AngII-induced atherosclerosis in LDL receptor-/-mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence [24][25][26] that increased MMP expression is associated with the development of neointimal lesions after arterial balloon injury in experimental animals. MMP inhibitor can suppress the development of intimal hyperplasia in hyperlipidemic rabbits [27]. However, other studies have demonstrated that doxycycline, a broadspectrum MMP inhibitor, has negligible effects on the development of AngII-induced atherosclerosis in LDL receptor-/-mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…To study the effect of the MMP inhibitor ONO-4817 against MMP-9 activity and small intestinal damage 24 h after administration of indomethacin, 100 mg/kg ONO-4817 (n ϭ 6) or placebo (n ϭ 6) was administered intraperitoneally 3 h before administration of indomethacin. The dose of ONO-4817 was determined on the basis of previous reports (Okamoto et al, 2007;Takai et al, 2007). The experimental procedures for the animals were conducted in accordance with the guidelines of Osaka Medical College.…”
Section: Methodsmentioning
confidence: 99%